Analisis Penerimaan Pengguna E-Toll Dengan Mengadopsi Model De Lone dan Mc Lean - Yoga Megasyah (FKOM UNIKU, 2019)
Technological developments are increasingly increasing specifically to facilitate transactionactivities. All parties in various fields continue to look for the latest for those who can provide the best forcustomers. Research conducted for toll road users in the city of Bandung, which aims to determine cellcomputerefficacy and perceived benefits of system quality, information quality, use, and satisfaction of tollroad users in using the e-toll payment system. The population of this study is the toll road users in the cityof Bandung. Samples taken 125 people were taken using nonprobability sampling technique. The resultsshowed that there were differences in cell-computer efficacy and perception of benefits for system quality,information quality, usage, and satisfaction of toll road users in using the e-toll payment system. Thissummary is taken based on the descriptive statistics produced.Keywords: computer self-efficacy and perceived benefits, system quality, information quality,use, and satisfaction of toll road users in using the e-toll payment system.